Comparative Analysis of Virulence Factors of Homozygous and Heterozygous Strains of Candida albicans Vaginal Isolates. (27th June 2020) - Nouraei, Hasti; Sheykhi, Sahar; ZareShahrabadi, Zahra; Khodadadi, Hossein; Zomorodian, Kamiar; Pakshir, Keyvan
Abstract : Although the epidemiology of pathogenic Candida species is changing due to invasive diseases, Candida albicans has become the common cause of human infections worldwide. Candida albicans is a diploid yeast with a mostly clonal mode of reproduction and without known complete sexual cycle. This species has two heterozygous and homozygous strains at hyphal wall protein 1 gene locus ( hwp1 ). Little is known about virulence factors of these strains. The aim of this study was to evaluate the exoenzyme activity of heterozygous and homozygous C. albicans strains. A total of 60 stock Candida albicans species isolates, which consisted of 30 homozygous and 30 heterozygous strains, were used for exoenzyme activities. We used egg yolk agar, Sabouraud blood agar, and bovine serum albumin agar for evaluation of phospholipase, hemolysin, and proteinase activity, respectively. Homozygous strains of Candida albicans had more phospholipase and proteinase activity than heterozygous strains. However, there were no significant statistical differences between the two strains in the severity of exoenzymes production. Beta hemolysin activity was seen in 100% and 96.7% of the homozygous and heterozygous strains, respectively. The results of this study indicated that both of the strains exhibited exoenzyme activities in different ranges. There were no significant statistical differences in virulence factors between the homozygous and heterozygous strains.